Assistance in Preparing Gender Responsive Village Budgets Towards Good Village Governance: Pendampingan Penyusunan Anggaran Desa Responsif Gender Menuju Good Village Governance - Ummul Fithriyyah, Mustiqowati; Zulhaida, Zulhaida (Universitas Lancang Kuning, 2024)
This research-based community service aims to provide assistance to village officials in the preparation of gender-responsive village budgets. This assistance is intended to provide understanding to the village community and especially to village government officials so that village funds can be used to develop gender-responsive village development programs. Gender responsive village budgets are a pillar in disseminating ideas that lead to improved village governance. This community service uses an Asset-based community development (ABCD) approach that emphasizes the assets and potential owned by Wonosari village, Rangsang district, MeraSSnti Islands regency. One of the things that is seen as an asset is the involvement of women in strategic positions as village government officials who handle village finances. In addition, the head of her village has had a gender justice perspective. The result of this community service is the achievement of changes in the understanding of village officials who already have a good understanding of gender response budgets